COMPARATIVE STUDY OF PROVERBS VERBALIZING THE CONCEPTUAL OPPOSITION"INTELLIGENCE/STUPIDITY" IN ENGLISH AND RUSSIAN (Scientific journal of the Fergana State University, 2025)
The article is devoted to a comparative study of the proverbs that verbalize the conceptual opposition "intelligence/stupidity" in English and Russian, in which the multi-level veralizers of this conceptual opposition, in particular proverbs, are analyzed, as a result of which their isomorphic and allomorphic features, as well as the factors determining the latter, are revealed.